FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA IBU HAMIL DI PUSKESMAS LANGSA LAMA KOTA LANGSA TAHUN 2015 - Lili Angriani Lubis; Zulhaida Lubis; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The pregnant woman with Chronic Energy Deficiency (CED) will birth a baby with low birth weight and risk of sudden mortality in prenatal. This condition, more of mother will died due to blooding and it will increase the mortality rate of neonate and mother. The objective of this research is to study factors related to the chronic energy deficiency event for pregnant woman, and this research was conducted at Puskesmas Langsa Lama, Langsa city. This research is analytic survey with cross sectional design. Sample in this research is 68 pregnant women, with questioner instrument to showed relationship of CED with pregnant woman with interview. The result of this research indicates that there was a correlation between knowledge and chronic energy deficiency incident that 29 pregnant woman with sufficiency knowledge with CED is 17.2 % while 21 of pregnant woman with low knowledge with CED is 76.2 %, with chi-square test (0.001). there is a correlation between income and CED incident to pregnant woman that indicates of 48 pregnant woman with the sufficient income with CED is 25 % and of 20 pregnant woman with low income and with CED 65 % with chi-square test (0.001). in addition, there is a correlation between the antenatal care assessment and CED incident to the pregnant woman. Of 24 pregnant women with antenatal care assessment with CED is 0%, while without assessment and with CED 48.0 % with chi-square test (0.001). It hope that the health staff at Langsa Lama Puskesmas can provide input and depiction about health condition ion provide the health extension and service for good nutrition supply for pregnant woman. It hopes to pregnant woman must be attention to their nutrition during the pregnancy. Keywords: Chronic Energy Deficiency (CED), Knowledge, Income, Antenatal Care